Suplementasi vitamin c dalam pakan sebagai upaya peningkatan kesehatan ikan mas (Cyprinus carpio L.) dalam menghadapi infeksi bakteri Aeromonas hydrophila: Vitamin-C suplement in fish feeding substance in order to improve carp fish health against aeromonas hydrophila bacterial infection - Agustina; Gina Saptiani; Rahmi Nohon (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
This study was conducted to determine the effects of different levels of vitamin C (ascorbic acid) supplementation on NVC (Nutrition Value Coeficient), clinical signs, pathological change, phagocytic index, antibody, and survival rate of fingerlings common carp (Cyprinus carpio L.). Three diets were formulated incorporating vitamin C at levels of 0 (control), 250 and 500 mg/ kg. Fish were randomly fed with the experimental diets for 35 days. On 15th day fish were injected intra muscular with 0.1 ml/fish, 106 CFU/ml concentration of A. hydrophila. The present study suggest that vitamin C concentration 250 mg/kg of diet most appropriate concentration, can enhance fish health (NVC), immune system (phagocytic index and antibody), survival rate, normal clinical signs and pathological change after infected by A. hydrophila.